PERCEIVED ALTERNATIVES OPPORTUNITY SEBAGAI PEMODERASI PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN CONSIGNMENT PT MATAHARI DEPARTEMENT STORE TBK. CABANG BENGKULU - Occy Rahmada Ningsih; Sugeng Susetyo; Paulus Suluk Kananlua (Management Insight: Jurnal Ilmiah Manajemen, 2020)
The purpose of this study is to determine the Perceived Alternatives Opportunitiy as   moderating the effect of job satisfaction on turnover intention in employee consignment  in  PT.  Matahari  Departement  Store  Tbk  Bengkulu  City.  This research use quantitative approach by using primary data collected by questionnaire. The sample is    consignment employees at PT. Matahari Departement Store Tbk Bengkulu City for amount 169 person taken using the sencus  method.  The  data  processing  technique  of  this  study  used  Statistical Package For Social Science (SPSS) software version 16.0. The analysis which is used including validity test and reliability test. The results of this study; 1) job satisfaction has a negative effect on Turnover Intention. 2) Job Satisfaction and Perceived Alternatives Opportunity affect Turnover Intention. 3) Perceived Alternatives  Opportunity  moderate the effect of  Job  Satisfaction  on  Turnover Intention.Keywords  :  Job  Satisfaction,  Perceived  Alternatives  Opportunity,  TurnoverIntention